2023
DOI: 10.3389/fnut.2023.1193289
|View full text |Cite
|
Sign up to set email alerts
|

“Medicine food homology” plants promote periodontal health: antimicrobial, anti-inflammatory, and inhibition of bone resorption

Abstract: “Medicine food homology” (MFH) is a term with a lengthy history. It refers to the fact that a lot of traditional natural products have both culinary and therapeutic benefits. The antibacterial, anti-inflammatory and anticancer effects of MFH plants and their secondary metabolites have been confirmed by numerous research. A bacterially generated inflammatory illness with a complicated pathophysiology, periodontitis causes the loss of the teeth’s supporting tissues. Several MFH plants have recently been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 167 publications
0
1
0
Order By: Relevance
“…In recent decades, extensive research has been conducted on the biological activity of dual-purpose materials and their metabolites. These studies have identified components such as polysaccharides, flavonoids, polyphenols, and saponins, demonstrating their vast potential in areas such as antioxidant activity, anti-aging, and prevention and treatment of various chronic diseases [23][24][25] . A notable discovery is the presence of lycibarbarspermidines in goji berries, which has been found to be effective in regulating and treating age-related neurodegenerative disorders [26] .…”
Section: Mfh Advancing In Technological Innovations For Scientific Br...mentioning
confidence: 99%
“…In recent decades, extensive research has been conducted on the biological activity of dual-purpose materials and their metabolites. These studies have identified components such as polysaccharides, flavonoids, polyphenols, and saponins, demonstrating their vast potential in areas such as antioxidant activity, anti-aging, and prevention and treatment of various chronic diseases [23][24][25] . A notable discovery is the presence of lycibarbarspermidines in goji berries, which has been found to be effective in regulating and treating age-related neurodegenerative disorders [26] .…”
Section: Mfh Advancing In Technological Innovations For Scientific Br...mentioning
confidence: 99%